2022
DOI: 10.26650/jepr950483
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of High-Technology Exports on the Growth of the Turkish Economy

Abstract: High technology product export is emerging as one of the issues that economists have discussed frequently in recent years. Increasing the high-tech product export performance provides a competitive advantage in international trade for countries. To this extent, this study aims to determine the impact of high technology product export on economic growth for Turkey over the period 1990-2019. For the empirical analysis, Hatemi-J ( 2008), Gregory and Hansen (1996) Fully Modified Ordinary Least Squares (FMOLS), DOL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…The convergence hypothesis, which is one of the main implications of the Solow model, is based on the assumption that technological change is external and constant between countries. Accordingly, per capita output levels of countries will approach each other, and the development differences will automatically disappear in the long term [35].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The convergence hypothesis, which is one of the main implications of the Solow model, is based on the assumption that technological change is external and constant between countries. Accordingly, per capita output levels of countries will approach each other, and the development differences will automatically disappear in the long term [35].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The ndings from a machine learning technique for verifying causality approach revealed that infrastructure affects economic growth. The policy implication suggested that lack of infrastructure maintenance eliminates the positive effects of investments and comparative advantage over time in the medium term Sofuoğlu et al (2022). explored the relationship between infrastructure (high technology) on economic growth employed the modi ed ordinary least square and canonical cointegration regression data from 1990 to 2019.…”
mentioning
confidence: 99%